2014
DOI: 10.1007/s10549-014-3033-4
|View full text |Cite|
|
Sign up to set email alerts
|

Platinum-based chemotherapy in triple-negative advanced breast cancer

Abstract: The purpose of this study was to evaluate the efficacy of platinum-based chemotherapy (PBC) versus conventional non-PBC regimens in a metastatic triple-negative breast cancer (TNBC) setting. We reviewed the electronic patient records of patients with confirmed metastatic TNBC at four major cancer centres in Canada. All patients were allocated into two groups based on type of chemotherapy received (PBC vs. non-PBC) and line of treatment (first-, second-, or third-line). The primary objective of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Interestingly, many of breast cancer patients with BRCA1 mutations have tumors that are triple-negative and particularly aggressive basal-like subtype [26, 34, 35]. Despite limited efficacy as a single agent in heavily treated metastatic breast cancers [35], carboplatin has shown to be an excellent addition to treatment regimen in TNBC, conferring increasing rates of pathological complete response and survival benefits to patients [13, 14, 36, 37]. Unfortunately, treatment failure is eventually seen in a substantial number of TNBC patients due to chemoresistance over time.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many of breast cancer patients with BRCA1 mutations have tumors that are triple-negative and particularly aggressive basal-like subtype [26, 34, 35]. Despite limited efficacy as a single agent in heavily treated metastatic breast cancers [35], carboplatin has shown to be an excellent addition to treatment regimen in TNBC, conferring increasing rates of pathological complete response and survival benefits to patients [13, 14, 36, 37]. Unfortunately, treatment failure is eventually seen in a substantial number of TNBC patients due to chemoresistance over time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ongoing clinical trials for metastatic TNBC are including platinum agents in their treatment regimens (4, 3638). In an orthotopic humanized breast-to-lung model, treatment with Nutlin-3a/carboplatin significantly inhibited primary tumor growth, and metastatic foci in the lung were fewer in number and smaller in size relative to treatment with vehicle or single-agent therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum agents, such as cisplatin and carboplatin, form DNA-platinum adducts resulting in intra- and interstrand DNA crosslinks leading to increased double strand breaks and cell death (3). Clinical studies have indicated that platinum-based therapy can provide enhanced efficacy in TNBC (4, 5). Furthermore, clinical trials are currently evaluating the utility of combination therapies that include carboplatin to specifically treat TNBCs with metastases (NCT01881230, NCT00691379, and NCT01281150; www.clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…Four studies (22)(23)(24)(25) reported that the overall survival (OS) rate was not significantly different between TNBC patients treated with a platinum-based regimen and those treated with a non-platinum-based regimen (P>0.05). So does the disease-free survival (DFS) rate according to three studies (Table II) (22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%